Vinland saga. Book eight - Yukimura, Makoto, 1976- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2016)
Free at last, Thorfinn sets off on an expedition to Vinland, to establish a place free of war and slavery. In an effort to fund his project, Thorfinn visits Iceland where Halfdan, a wealthy man who shared a dark history with his late father, awaits. Meanwhile, the marriage between Halfdan's son Sigurd and Leif's relative Gudrid are well under way, but Gudrid dreams of becoming a sailor, not a bride. A battle soon breaks out as Gudrid attempts to escape aboard Leif's ship. With Sigurd hot at their tail, Thorfinn and the crew press eastward to the city of Miklagard, picking up an orphaned baby and a dog along the way;